FACTORS INFLUENCING MILK PRODUCTION OF LOCAL GOATS OF ROHILKHAND REGION OF UTTAR PRADESH UNDER SEMI INTENSIVE SYSTEM - UPADHYAY, D.; PATEL, B.H.M.; KERKETTA, S.; BHARTI, P.; SAHU, S.; BHUSAN, B. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTAn investigation was undertaken to study the effect of season, parity, type of birthand teat abnormality on milk yield of local goats of Rohilkhand region. A total of 32 doeswere selected for the experiment, and were grouped according to season (rainy and winter),parity (primiparous and multiparous), type of birth (single and twin), and type of teatabnormality (normal teat and abnormal teat). All does were milked twice daily and milk yieldwas recorded up to 90 days. It was found that average daily milk yield (ADMY) and total milkyield of 90 days (TMY) were significantly (P